Analytical solution for one-dimensional electro-osmotic consolidation of double–layered system - Zhao, Xu-Dong; Liu, Yang; Gong, Wen-Hui (Computers and geotechnics, 2020)
Electro-osmotic consolidation can be used as a valid and innovative technique for ground improvement. Considering the limitation of previous studies that layered soil heterogeneity was not taken into account, this paper presented an analytical model for one-dimensional(1D) electro-osmotic consolidation of double-layered soil, and a computer program of fully explicit solutions for excess pore pressure and degree of consolidation was developed. In order to validate its accuracy, a series of verification examples were conducted using analytical approach and the finite difference method. Comparison results demonstrated excellent accuracy of the proposed solutions. Furthermore, parametric studies were conducted to investigate the influence of relative permeability and compressibility relationship on the consolidation behavior. It can be found that the differences of hydraulic conductivities and electro-osmosis conductivities in the two layers will lead to a sharp change of the excess pore pressure profiles at the interface of two layers. A larger value of coefficient of volume compressibility in the second layer will slow down the dissipation process of excess pore pressure. A thicker layer with higher compressibility will result in a slower the rate of dissipation of the excess pore pressure, and a thicker layer with higher permeability causes a smaller value of the excess pore pressure, while in the layer of lower permeability, the opposite occurs.